[N2C6H14](2)[(UO2)(6)(H2O)(2)F-2(PO4)(2)(HPO4)(4)]center dot 4H2O: A new microporous uranium phosphate fluoride - Doran, M; Stuart, C; Norquist, A; O'Hare, D (2004)
A new three-dimensional uranium compound is reported, [N2C 6H14]2[(UO2)6(H 2O)2F2(PO4)2-(HPO 4)4]·4H2O. This is the first in a new family of microporous materials, organically templated uranium phosphate fluorides, and contains multiple channels that are connected in three dimensions.